2022
DOI: 10.1002/jso.26987
|View full text |Cite
|
Sign up to set email alerts
|

A novel limb‐salvage reconstruction strategy with a custom hemipelvic endoprosthesis and preserved femoral head following the resection of periacetabular tumors: A preliminary study

Abstract: The treatment of periacetabular malignancy frequently challenges surgeons. To simplify the surgical procedure, we performed a novel reconstruction strategy preserving the femoral head for patients with periacetabular malignancies. We retrospectively reviewed 14 patients who underwent total en bloc resection of a periacetabular tumor and reconstruction of the hip joint with an individualized hemipelvic endoprosthesis and remaining femoral head from July 2015 to January 2019 at our center. Regions of pelvic rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Rizkallah et al reported on the medium-term outcomes of pelvic reconstruction utilizing the LUMiC endoprostheses (Implantcast) and demonstrated low rates of aseptic loosening, with dislo-cation and infection being the most common major complications 12 . Xie et al evaluated the utility of a custom hemipelvic endoprosthesis with preservation of the femoral head in patients with primary bone malignancies and found acceptable function and oncologic outcomes at an early follow-up 13 . Hinckley et al retrospectively reviewed patients who underwent pelvic reconstruction with a custom ilium monoflange prosthesis 14 .…”
Section: Pelvic Reconstructionmentioning
confidence: 99%
“…Rizkallah et al reported on the medium-term outcomes of pelvic reconstruction utilizing the LUMiC endoprostheses (Implantcast) and demonstrated low rates of aseptic loosening, with dislo-cation and infection being the most common major complications 12 . Xie et al evaluated the utility of a custom hemipelvic endoprosthesis with preservation of the femoral head in patients with primary bone malignancies and found acceptable function and oncologic outcomes at an early follow-up 13 . Hinckley et al retrospectively reviewed patients who underwent pelvic reconstruction with a custom ilium monoflange prosthesis 14 .…”
Section: Pelvic Reconstructionmentioning
confidence: 99%
“…The reconstruction of the pelvis following internal hemipelvectomy has been an area of intense clinical review. Reconstruction options that have been reported to have reasonable surgical outcomes, albeit with high complication rates, include double-barreled free vascularized fibular grafting, structural allograft, individualized hemipelvic prosthesis, an ice-cream cone prosthesis, and personalized 3-dimensional (3D) printing-based limb salvage and reconstruction implants 2,4,5,10,12,14 . A few studies have identified risk factors for poorer oncologic and surgical outcomes in pelvic tumors.…”
Section: Primary Bone Tumorsmentioning
confidence: 99%